Probiotics as Alternatives to Antibiotic Growth Promoters in ISA Brown Males Chicken - Afililla, Zhaza; Agustono, Bodhi; Marbun, Tabita Damaria; Vedy, Dayang Urmila Shahnaz; Yulisah, Dina; Riastianto, Muhammad Rofiq; Firmansyah, Muhammad Alif Rifqi; Farihah, Diniah Umy; Zahra, Reyza Miladiya Khuriyah; Afandik, Nadya Ashila; Ghultom, Astri Agustina; Meiliza, Nazwa; Nugroho, Adi; Prima, Jaya Agusc (Media Kedokteran Hewan, 2026)
Antibiotic Growth Promoters (AGP/AGPs) have been used to improve feed efficiency in poultry, but are banned in Indonesia due to food safety concerns. This study evaluated the potential of probiotics as an AGP alternative in ISA Brown male layer chickens during the finishing period, focusing on blood glucose and cholesterol levels. A total of 180 chickens were reared for 42 days. Treatment groups received basal feed supplemented with probiotics at 1–5 mL/kg, equivalent to 1.2×10⁹ to 6×10⁹ CFU/kg feed, containing Lactobacillus acidophilus, Lactobacillus plantarum, and Bifidobacterium spp. Blood cholesterol was analysed using an enzymatic colorimetric method at 500 nm, while glucose was measured using the glucose oxidase method at 505 nm. Results showed that probiotic treatments (P2, P3, P5) significantly reduced glucose levels compared to the control (P0) and AGP group (P1). A moderate decrease in cholesterol levels was also observed in probiotic groups. These effects may be linked to improved gut microbial balance and nutrient metabolism. The probiotic combination used in this study shows potential as a safer and more sustainable alternative to AGPs. Further studies are recommended to optimize dosage and assess long-term impacts on poultry health and productivity.